Study about 3D QSAR of Pyrrolo Pyrimidine and Thieno Pyrimidines as Human Thymidylate Synthase Inhibitors - K. Meena Kumari; L. Yamini; M. Vijjulatha (Current Topics on Chemistry and Biochemistry Vol. 8, 2023)
The present studies established that CoMFA and CoMSIA models are quite reliable to efficiently guide further modification in the molecules for obtaining better drugs. The enzyme thymidylate synthase (TS) is essential for the synthesis of DNA, and numerous nonclassical lipophilic antifolates that target this enzyme are effective and promising as antitumor medications. We report 3D-QSAR analyses on pyrrolo pyrimidine and thieno pyrimidine antifolates to contemplate the mechanism of action and structure-activity relationship of these molecules. By applying leave-one-out (LOO) cross-validation study, cross-validated q2 value of 0.523 and 0.566 for CoMFA Ligand based(LB) and Receptor based(RB), 0.516 and 0.471 for CoMSIA LB and RB respectively. while the non-cross-validated r2 values were found to be 0.974 and 0.969 for CoMFA LB and RB, 0.983 and 0.972 for CoMSIA LB and RB respectively. The models were graphically interpreted using CoMFA and CoMSIA contour plots. The results obtained from this study were used for rational design of potent inhibitors against thymidylate synthase. The 3D-QSAR results identified some key locations where steric, hydrogen-bond donor modifications should have a significant impact on the molecules’ bioactivities. These hints were used to develop novel, high-affinity human thymidylate synthase inhibitors, which have the potential to be effective cancer treatment agents.